2009
DOI: 10.1088/0022-3727/43/2/022001
|View full text |Cite
|
Sign up to set email alerts
|

Metal vapour causes a central minimum in arc temperature in gas–metal arc welding through increased radiative emission

Abstract: A computational model of the argon arc plasma in gas–metal arc welding (GMAW) that includes the influence of metal vapour from the electrode is presented. The occurrence of a central minimum in the radial distributions of temperature and current density is demonstrated. This is in agreement with some recent measurements of arc temperatures in GMAW, but contradicts other measurements and also the predictions of previous models, which do not take metal vapour into account. It is shown that the central minimum is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 27 publications
(31 reference statements)
8
60
0
9
Order By: Relevance
“…Therefore the use of a turbulence model is in fact not necessary, and will not influence our results; this is in accordance with the findings for modelling of a single gas-metal arc [37].…”
Section: Arc Behaviour and Interactionssupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore the use of a turbulence model is in fact not necessary, and will not influence our results; this is in accordance with the findings for modelling of a single gas-metal arc [37].…”
Section: Arc Behaviour and Interactionssupporting
confidence: 89%
“…The calculated maximum temperature is 18 000 K and the maximum plasma velocity is about 215 m/s. As for all the temperatures presented in this paper, we would expect the effects of metal vapour to decrease this value, since it has been shown that the increased radiative emission due to the presence of metal vapour emanating from the wire electrodes has this effect [18,37,38].…”
Section: Arc Behaviour and Interactionsmentioning
confidence: 86%
See 1 more Smart Citation
“…The analysis was performed by means of a magneto-hydrodynamic arc model previously developed by Schnick et al [22][23][24]. This model was originally applied for the simulation of the arc behaviour during pure arc welding processes such as tungsten inert-gas (TIG) and gas metal-arc (GMA) welding and implemented using the commercial software package Ansys CFX.…”
Section: Numerical Analysis Of Particular Laser-arc Interaction Phenomentioning
confidence: 99%
“…Thus net emission coefficients remain important input data for numerical modelling of welding arcs as done by e.g. Lowke et al [4] and Schnick et al [5]. The use of net emission coefficients in such models has the drawback that it does not take into account the inhomogeneity of the temperature and the spatial distribution of the elements in experimental arcs.…”
Section: Introductionmentioning
confidence: 99%